Bioethics in complexity : foundations and evolutions - De Risio, Sergio, 1945-; Orsucci, Franco (Imperial College Press ; Distributed by World Scientific Pub., 2004)
This publication reviews the foundations of ethics in the history ofWestern thinking. It connects these philosophical matters withevolutionary theory and contemporary bioethics, biology and medicine, posing new questions for the current dialectics between categoricaland contextual ethics. Novel answers are presented from complexitytheory self-organization and nonlinear dynamics.